Protectiveness of Banana Peel Extract Lotion (Musa x paradisiaca L.) as Aedes aegypti Mosquito Repellent - Nurul Apriani Adinda; Endah Setyaningrum; Nuning Nurcahyani; Emantis Rosa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Dengue Hemorrhagic Fever (DHF) is an illness that is brought about by the dengue virus and transmitted through female Aedes aegypti mosquitoes. The majority of repellents that are available in the market contain hazardous synthetic chemicals, including N,N-diethyl-meta-toluamide (DEET). Isoamyl acetate and saponins, which have the potential to repel insects, are present in the extract of kepok banana peel. The aim of this research was to ascertain the level of protective ability, Effective Time 50% (ET50), Effective Concentration 50% (EC50), physical stability and irritation effect of kepok banana peel ethanol extract lotion. The methodology utilized in this study adheres to the World Health Organization Pesticides Evaluation Scheme (WHOPES) guidelines and employs a randomized design approach. The level of protection provided by the ethanol extracts from kepok banana peels was assessed through a one-way ANOVA, followed by the BNT 5% test and probit analysis. Based on the findings, it was discovered that the concentration levels of 12,5%, 25%, and 50% provided a protective ability of 22,91%, 59,78%, and 80,30%, correspondingly, with an EC50 value of 27,80% and ET50 observed at the 11th minute. This lotion exhibits excellent physical stability and does not elicit any skin irritation. To conclude, the lotion containing ethanol extract from kepok banana peel has the potential to serve as an Aedes aegypti mosquito repellent. However, there is a need for probandus criteria based on age, gender and skin type in future studies.